Configurational demographic predictors of work–nonwork satisfaction - Farivar, F.; Richardson, Julia (WILEY, 2020)
© 2019 John Wiley & Sons Ltd Contemporary work–life balance research tends to treat demographic variables as moderators, grouping variables, or control variables influencing work and nonwork satisfaction. Yet earlier theories were premised on the assumption that they are, in fact, predictors of work and nonwork satisfaction even though those assumptions have not yet been tested empirically. Drawing on an Australian study comprising 798 white-collar employees and using a fuzzy-set qualitative comparative analysis technique, we investigate demographic variables as potential configurational predictors affecting work–nonwork satisfaction, defined as a combination of work satisfaction and nonwork satisfaction. The analysis revealed different scenarios and specific patterns between configurational solution terms leading to work–nonwork satisfaction. Employment status and age of children (specifically age differences between children) were the most important demographic variables influencing employees' work–nonwork satisfaction.